Benchmarking clinical photography services in the NHS. (2nd October 2015) - Arbon, Giles
Abstract : Benchmarking is used in services across the National Health Service (NHS) using various benchmarking programs. Clinical photography services do not have a program in place and services have to rely on ad hoc surveys of other services. A trial benchmarking exercise was undertaken with 13 services in NHS Trusts. This highlights valuable data and comparisons that can be used to benchmark and improve services throughout the profession.